2014
DOI: 10.1071/an14479
|View full text |Cite
|
Sign up to set email alerts
|

Influencing the future: interactions of skeleton, energy, protein and calcium during late gestation and early lactation

Abstract: Marked improvements in milk production, health and reproduction have resulted from manipulations of the pre-calving diet. An understanding of the underlying physiological changes resulting from manipulation of late gestational diets is needed in order to refine and enhance these responses. The physiology of late gestation and early lactation of the dairy cow is examined in the context of exploring the hypothesis that changes in physiology occur not only through homeostatic, but also homeorhetic change. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 99 publications
2
43
0
Order By: Relevance
“…These diets, fed for a limited time before calving, have a prolonged positive effect on dairy cow production and health that extends into lactation (Block, 1984;DeGroot et al, 2010). Lean et al (2014) found that when diets with lower DCAD (mEq/kg) were fed before calving, milk yield increased in multiparous but not nulliparous cows. Lean et al (2014) suggested that the mechanisms that lead to prolonged milk yield responses and better health following a limited period, typically 25 d, of feeding diets lower in DCAD require further exploration to both understand and possibly enhance these responses.…”
Section: Introductionmentioning
confidence: 99%
“…These diets, fed for a limited time before calving, have a prolonged positive effect on dairy cow production and health that extends into lactation (Block, 1984;DeGroot et al, 2010). Lean et al (2014) found that when diets with lower DCAD (mEq/kg) were fed before calving, milk yield increased in multiparous but not nulliparous cows. Lean et al (2014) suggested that the mechanisms that lead to prolonged milk yield responses and better health following a limited period, typically 25 d, of feeding diets lower in DCAD require further exploration to both understand and possibly enhance these responses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bone calcium and glucose are causally linked through osteocalcin and insulin metabolism, as was shown in murine studies (Lee et al, 2007), and reviewed in a bovine context (Lean et al, 2014). Elegant intervention studies by Martinez et al (2014) demonstrated the central role of hypocalcaemia in influencing insulin and glucose concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…Good nutritional management of dairy cattle during the transition period can improve their responses to the metabolic challenges posed by late pregnancy and early lactation (Bell, 1995;Lean et al, 2014). Hence, metabolic status and dietary interventions before calving are valuable to study as predictors of future productivity and reproductive performance (Bell, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that in last weeks of pregnancy and at the beginning of lactation, high energy demand intensify maternal https://doi.org/10.33785/IJDS.2019.v72i04.007 metabolism due to augmented mitochondrial activity in maternal tissues (Aurousseau et al 2006). The imbalance between the rate of ROS production and their neutralization lead to the oxidative stress and increase antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (Lean, 2014). Therefore, production of ROS during late gestation and early lactation is intensified and it is reasonable to assume that the high BCS combined with high milk yield in the previous lactation might result in higher metabolic and oxidative stress (Castillo, 2005;Pedernera et al 2010).…”
Section: Introductionmentioning
confidence: 99%